1996
DOI: 10.1007/bf01736990
|View full text |Cite
|
Sign up to set email alerts
|

Application of α-aminoisobutyric acid,l-methionine, thymidine and 2-fluoro-2-deoxy-d-glucose to monitor effects of chemotherapy in a human colon carcinoma cell line

Abstract: Up to 4 h after treatment of human SW 707 colon carcinoma cells with the antineoplastic drug 4-amino-N-(2'-aminophenyl)-benzamide (GOE 1734, dinaline), the effects of tumour cell metabolism and proliferation were examined in vitro. Four tracers which can be labelled with isotopes suitable for positron emission tomography (PET) were used for this purpose: alpha-aminoisobutyric acid (AIB) and methionine to study changes in amino acid transport and protein synthesis, thymidine to observe changes in tumour prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Although damaged neuronal areas are expected to be detected from lower [ 18 F]FDG uptake than that in intact area, several limitations of [ 18 F]FDG, such as uptake by foci of infection and/or inflammation (Kubota et al, 1992; Yamada et al, 1995), might provide incorrect results of neuronal damage. In tumor imaging with PET, it is well known that [ 18 F]FDG exhibits a lower sensitivity and/or specificity for the assessment of chemotherapy (Haberkorn et al, 1997; Schaider et al, 1996) and radiation therapy (Murayama et al, 2009; Sugiyama et al, 2004), all of which induce inflammation response in tissues. In contrast to tumor imaging, little evidence has been reported on how inflammatory activation in the brains affected by neurodegenerative diseases influences the results of [ 18 F]FDG‐PET.…”
Section: Discussionmentioning
confidence: 99%
“…Although damaged neuronal areas are expected to be detected from lower [ 18 F]FDG uptake than that in intact area, several limitations of [ 18 F]FDG, such as uptake by foci of infection and/or inflammation (Kubota et al, 1992; Yamada et al, 1995), might provide incorrect results of neuronal damage. In tumor imaging with PET, it is well known that [ 18 F]FDG exhibits a lower sensitivity and/or specificity for the assessment of chemotherapy (Haberkorn et al, 1997; Schaider et al, 1996) and radiation therapy (Murayama et al, 2009; Sugiyama et al, 2004), all of which induce inflammation response in tissues. In contrast to tumor imaging, little evidence has been reported on how inflammatory activation in the brains affected by neurodegenerative diseases influences the results of [ 18 F]FDG‐PET.…”
Section: Discussionmentioning
confidence: 99%
“…A number of benzamide derivatives have been shown to possess the properties of antitumor activity or sensitization of cytotoxicity induced by chemo-or radiotherapies both in vitro and in vivo (7,15,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). The mechanism of action that has so far been attributed to this class of agents can be conveniently divided into two pharmacological categories: namely (a) the non-N-substituted benzamides and nicotinamides which can alter tumor blood flow and thus increase DNA damage and sensitizes (32) and (b) the N-substituted benzamides and nicotinamides which can inhibit DNA repair, increase DNA damage, induce apoptosis and thereby sensitize (12, 13.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have used radiolabeled AIB for tumor imaging in animal models of brain and systemic tumors, including rodents with implanted glioma, colon, melanoma, and prostate tumors as well canines with spontaneously occurring tumors . In these studies, AIB generally demonstrated good tumor imaging properties, although the uptake in the spontaneous canine tumors was variable.…”
Section: Fluorine‐18 and Radioiodinated αα‐Dialkyl Amino Acidsmentioning
confidence: 99%